SOCIAL MATURITY AND THE MARRIAGE OF AISHA BINT ABU BAKR (D. 58 AH / 678 AD): A SOCIOLOGICAL STUDY IN THE CONTEXT OF THE PRE-ISLAMIC AND EARLY ISLAMIC ERAS - Sedeeq, Jotyar (Humanities Journal of University of Zakho, 2026)
This study focuses on the phenomenon of the marriage of ʿĀʾisha bint Abī Bakr within a historical-sociological framework, drawing upon conceptions from the philosophy of history, which regard social phenomena as the outcome of a complex interplay between social structures, collective imagination, and cultural representations. According to this view, an event can only be fully understood in light of the context in which it emerged, requiring a departure from present-day moral standards in favor of exploring the cognitive and value systems that governed collective and individual behavior in their original historical settings. The central problem of the study lies in questioning whether ʿĀʾisha’s marriage represents a continuation of the early marriage patterns prevailing in pre-Islamic Arab society, or whether it has undergone religious and historical reinterpretation within various authoritative and epistemological frameworks. The study adopts a sociological-analytical methodology, drawing on structural-functional approaches and the classical theories of Émile Durkheim, Talcott Parsons, and Pierre Bourdieu to examine the relationship between social structure and individual behavior. This requires a systematic distinction between “marriage as a text” and “marriage as a reality,” that is, the necessity of the chapter to separate the rulings stipulated by legitimacy texts from the practices imposed by social contexts. and that requires working on the historical layers of the text and context, the study entitled (Social Maturity and the Marriage of Aisha bint Abi Bakr (d. 58 AH/678 AD)), is a sociological study in a modern context (pre-Islamic and early Islamic) consisting of two sections. The first section tackles the concept of social maturity, the patterns of marriage in Arab society before Islam, and what was approved in Islam briefly, with a concise presentation of the early biography of Aisha bint Abi Bakr and the controversy of her age of marriage as mentioned in historical and jurisprudential sources. While the second section discusses the early marriage issue within its historical context and analyzes it sociologically in light of the prevailing value structures at that time.